Fake Me If You Can: Unforgeable Digi-Physical Academic Certificates With Instant Verifiability - Laltu Sardar (IEEE Access, 2025)
Academic certificate forgery is a significant societal issue that impacts immigration controls and competitive job markets. Existing physical certificate verification processes are inefficient, relying heavily on manual methods, requiring substantial time and human resources, and are further complicated by cross-border challenges such as data protection laws. While robust blockchain-based certificate management solutions exist and are well-suited for environments where regulatory trust is lacking, their cost and complexity make them less attractive in settings where regulatory bodies are already trusted. In such practical contexts, certificate verification can be performed efficiently without the overhead associated with blockchain technologies. In this work, we introduce FastVer, a cryptographically secure, novel certificate verification framework that enables instant verification of issued certificates at the global cross-border level, as well as at domestic and university levels. Moreover, under a stronger adversarial model, we invoke the IbSM tree and propose SFastVer, a novel framework capable of revoking previously issued certificates that were authorized but issued in an unauthorized manner. Both frameworks seamlessly integrate into existing systems and policies with minimal disruption. Verification within this framework is cost-free, and maintenance costs remain remarkably low. We implement prototypes of both frameworks. The experimental results demonstrate that they are fast, highly scalable, and efficient, achieving verification times of just a few seconds per certificate.